The facilitation of professional values amongst student nurses in the North-West Province - I Mogodi; K Jooste; A C Botes (AOSIS, 2003)
The purpose of this study was to formulate guidelines to facilitate the internalisation of professional values in student nurses in order to enable them to become caring registered nurses. Opsomming Die doel van hierdie studie was om riglyne te formuleer om die internalisering van professionele waardes in studenteverpleegkundiges te fasiliteer wat hulle in staat sal stel om praktisyns wat omgee, te word. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.